TINJAUAN SIYASAH SYAR’IYYAH TERHADAP UPAYA PERLINDUNGAN SUNGAI PARANGKEKE KECAMATAN TELLULIMPOE KABUPATEN SINJAI - Hidayat, Azhar; Kurniati, Kurniati (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2022)
The purpose of this study is to find out how the protection of the Parangkeke River, Tellulimpoe District, Sinjai Regency is carried out using qualitative field methods. The results of this study show that the pollution of the Parangkeke River is caused by factory waste, household waste and agricultural waste. The Sinjai Regency Government has tried to handle the Parangkeke River pollution case with several steps, namely facilitating the settlement of environmental disputes, issuing environmental permits, supervising activities, issuing PPLHD permits, compiling means of preventing pollution and environmental damage and providing warnings of pollution and environmental damage. Protecting the environment is a collective responsibility and obligation because damage on earth does not just happen without human intervention, and the condition has been affirmed in the Qur'an that all damage that occurs both on earth and in the sea is the result of the deeds of human hands.